Adopting the CSR Route for Corporate Image Building: A Case Study on the Indian Steel Industry - Dokania, Abhishek Kumar; Pathak, Govind Swaroop (Prabandhan: Indian Journal of Management, 2015)
Corporate social responsibility is recognized as a significant tool to enhance a company’s image as well as reputation. In the globalized, connected world of today, a discernment of positive corporate image as regards to various stakeholders has become crucial for the success of any organization. Evidence shows that a positive corporate image provides a significant competitive advantage to the company and acts as a differentiator as compared to its competitors. The objective of this paper is to examine, by using the case study method, the CSR initiatives adopted by select Indian steel manufacturing organizations, and how these initiatives have helped them enhance their corporate image. Based on the findings of the present study, managerial implications and suggestions for further research in this field have been provided.